Malignancy incidence and primary tumor investigation in the patients with vertebral compression fractures by means of combined Tc-99m methylene diphosphonate bone scintigraphy and fluorodeoxyglucose positron emission tomography/computed tomography - Zehra Pınar Koç; Pelin Özcan Kara; Ahmet Dağtekin; Gülhan Örekici (Journal of Radiation and Cancer Research, 2022)
Purpose: Vertebral compression fractures frequently present with back pain and are determined by magnetic resonance (MR) imaging. However, fluorodeoxyglucose positron emission tomography/computed tomography (FDG PET/CT) is performed to determine the pathological fractures and primary tumors in a single imaging modality. The aim of this study is to evaluate the incidence of pathological fractures and primary tumors by means of combined bone scintigraphy and FDG PET/CT. Materials and Methods: Twenty-eight patients (15 females, 13 males; mean: 67.8 ± 11.6 years) with compression fractures determined by MR or plain radiographs were the subject of this study. The patients were referred for whole-body bone scintigraphy and due to the suspicion of metastasis additional FDG PET/CT was performed. The results of both studies were compared with the pathological and/or follow-up results. Results: The bone scintigraphy and PET/CT did not reveal concordant results according to the Kappa test. The SUVmax cutoff value was accepted as “7” and with this cutoff value, PET/CT achieved 57.1% sensitivity and 95.2% specificity in the determination of pathologic compression fractures. Conclusion: Although the results of bone scintigraphy and FDG PET/CT were not correlated with each other, FDG PET/CT revealed high specificity in the detection of pathologic fractures.